Lens-induced glaucoma in the elderly - Dimitris Papaconstantinou (Dove Medical Press, 2009)
Dimitris Papaconstantinou, Ilias Georgalas, Nikos Kourtis, Augustine Krassas, Andreas Diagourtas, Chrysanthi Koutsandrea, Gerasimos GeorgopoulosDepartment of Ophthalmology, University of Athens, Athens, GreeceAbstract: Lens-induced glaucoma comprises a number of different glaucomatous processes occurring in the elderly that share in common the role of the crystalline lens in the mechanism of increase in intraocular pressure. We will review the anatomic predisposing factors, their physiology, signs and symptoms, and therapeutic approach. We will consider two studies and discuss the visual results and risk factors associated with these pathologic conditions.Keywords: glaucoma, intraocular pressure